Controlled-release urea reduces nitrogen fertilizer-induced proton release: a column experiment - Zong, Haolin; Zou, Peng; Sun, Yunbao; Li, Jianghua; Wang, Chun; Zheng, Wenkui (Frontiers in Soil Science, 2026)
Nitrogen (N) fertilization is a major driver of soil acidification, yet quantitative evidence on how controlled-release urea (CRU) alters H+ production (Hpro) pathways remains limited. We conducted a 90-day soil column experiment using a calcareous fluvo-aquic soil collected from a 14-year long-term field site. Five treatments were established with four replicates: no N (CK), full- and high-rate CRU (CRF1 and CRF2), and full- and high-rate conventional urea (BBF1 and BBF2). Leachates were collected on days 7, 30, 60 and 90 and analyzed for inorganic N, major cations and anions. The Hpro was quantified using an input-output balance approach by separating the N-cycle component (associated with net NO3− export) and the carbonate-related C-cycle component (associated with net HCO3− export). Compared with conventional urea at the same N rate, CRU reduced cumulative NO3− leaching by 54.17% (CRF1 vs. BBF1) and 44.93% (CRF2 vs. BBF2), accompanied by lower base-cation losses. Total Hpro over 90 days decreased by 42.47% (CRF1 vs. BBF1) and 33.66% (CRF2 vs. BBF2). These results indicate that CRU mitigates fertilizer-induced acidification potential mainly by moderating nitrification-driven NO3− losses and associated charge-balanced cation leaching, thereby lowering the net H+ load exported from the soil profile.